Surface Electric Fields Increase Human Osteoclast Resorption through Improved Wettability on Carbonate-Incorporated Apatite - Bergara-Muguruza Leire; Mäkelä Keijo; Yrjälä Tommi; Salonen Jukka; Yamashita Kimihiro; Nakamura Miho (American Chemical Society, 2022)
Osteoclast-mediated bioresorption can be an efficient means of incorporating the dissolution of biomaterials in the bone remodeling process. Because of the compositionally and structurally close resemblance of biomaterials with the natural mineral phases of the bone matrix, synthetic carbonate-substituted apatite (CA) is considered as an ideal biomaterial for clinical use. The present study therefore investigated the effects of electrical polarization on the surface characteristics and interactions with human osteoclasts of hydroxyapatite (HA) and CA. Electrical polarization was found to improve the surface wettability of these materials by increasing the surface free energy, and this effect was maintained for 1 month. Analyses of human osteoclast cultures established that CA subjected to a polarization treatment enhanced osteoclast resorption but did not affect the early differentiation phase or the adherent morphology of the osteoclasts as evaluated by staining. These data suggest that the surface characteristics of the CA promoted osteoclast resorption. The results of this work are expected to contribute to the future design of cell-mediated bioresorbable biomaterials capable of resorption by osteoclasts and of serving as a scaffold for bone regeneration.